When fate hands you lemons: A moderated moderation model of bullying victimization and psychological distress among Chinese adolescents during floods and the COVID-19 pandemic - Zhang, Yuchi; Jia, Xiaoyu (Frontiers in Psychology, 2023)
Background: Bullying is a serious global issue with a number of negative mental health consequences for victims. Although the associations between bullying victimization in schools and adolescent psychological distress are well established, few studies have explored psychological distress in relation to combined interpersonal, peer, and cultural factors using a social-ecological system framework in Eastern contexts. Negotiable fate is a cultural belief common in Eastern societies that suggests that people can negotiate with fate for control by exercising personal agency within the limits that fate has determined. This study examined the moderating effects of neuroticism and negotiable fate on the relationship between bullying victimization and psychological distress among Chinese adolescents. Moreover, human society commonly suffers from multiple disasters that lead to severe mental health outcomes, and there are few empirical studies on the effects of bullying victimization outcomes among adolescents in multiple disaster contexts. This study included participants who experienced floods and the coronavirus disease 2019 (COVID-19) simultaneously in 2021. Materials and Methods: We conducted a cross-sectional cluster sampling study from August 6 to 9, 2021, approximately two weeks after the start of the Zhengzhou city flooding and seven days after the new wave of the COVID-19 outbreak in Zhengzhou City. The study included 1,207 participants (52.4% men, n = 633; Mage = 14.36, SD = .94) from a middle school in Zhengzhou City, China. Results: The results revealed that bullying was positively linked to psychological distress (β = .5.34, p < .001, [.73, 9.95]). Neuroticism and negotiable fate significantly moderated the relationship between the effects of bullying and psychological distress (β = -3.58, p <.05, 95% CI [-6.12, -1.04]). Specifically, high neuroticism increased the risk of psychological distress in adolescents bullied before a disaster. High or low neuroticism and high negotiable fate buffered the link between bullying and psychological distress. Conclusions: This study showed that neuroticism and negotiable fate moderated the relationship between bullying victimization and psychological distress in Chinese students with COVID-19 and flood disasters. High negotiable fate and high or low neuroticism could help adolescents bullied in school to be immune from psychological distress in catastrophe.